Epigenetic signature of chronic low back pain in human T cells. (3rd November 2021) - Grégoire, Stéphanie; Cheishvili, David; Salmon-Divon, Mali; Dymov, Sergiy; Topham, Lucas; Calderon, Virginie; Shir, Yoram; Szyf, Moshe; Stone, Laura S.
Abstract : Supplemental Digital Content is Available in the Text. This study reveals sex-specific DNA methylation signatures in human T cells that discriminate chronic low back pain participants from healthy controls. Abstract: Objective: Determine if chronic low back pain (LBP) is associated with DNA methylation signatures in human T cells that will reveal novel mechanisms and potential therapeutic targets and explore the feasibility of epigenetic diagnostic markers for pain-related pathophysiology. Methods: Genome-wide DNA methylation analysis of 850, 000 CpG sites in women and men with chronic LBP and pain-free controls was performed. T cells were isolated ( discovery cohort, n = 32) and used to identify differentially methylated CpG sites, and gene ontologies and molecular pathways were identified. A polygenic DNA methylation score for LBP was generated in both women and men. Validation was performed in an independent cohort ( validation cohort, n = 63) of chronic LBP and healthy controls. Results: Analysis with the discovery cohort revealed a total of 2, 496 and 419 differentially methylated CpGs in women and men, respectively. In women, most of these sites were hypomethylated and enriched in genes with functions in the extracellular matrix, in the immune system (ie, cytokines), or in epigenetic processes. In men, a unique chronic LBP DNA methylation signature was identified characterized by significant enrichment for genes from the major histocompatibility complex. Sex-specific polygenic DNA methylation scores were generated to estimate the pain status of each individual and confirmed in the validation cohort using pyrosequencing. Conclusion: This study reveals sex-specific DNA methylation signatures in human T cells that discriminates chronic LBP participants from healthy controls.